Dietary Tea Polyphenols Improve Growth Performance and Intestinal Microbiota Under Chronic Crowding Stress in Hybrid Crucian Carp - Zhe Yang; Gege Sun; Jinsheng Tao; Weirong Tang; Wenpei Li; Zehong Wei; Qifang Yu (Animals)
This study systematically investigated the effects of dietary tea polyphenols (TPs, major bioactive polyphenols from Camellia sinensis with potent antioxidant and anti-inflammatory properties) on the growth performance and intestinal health of hybrid crucian carp HCC2 under chronic crowding stress. A low-density control group (44.4 fish/m3, basal diet without TPs) and four high-density crowding stress groups (222.2 fish/m3) were established, one fed the basal diet without TPs (CS) and three fed basal diets supplemented with 100 (CSLTP), 200 (CSMTP), or 400 (CSHTP) mg/kg TPs. We analyzed the impacts of TPs on growth performance, serum biochemical parameters, antioxidant capacity, expression of lipid metabolism-related genes, and intestinal microbiota composition. The results demonstrated that chronic crowding stress significantly suppressed the final body weight, weight gain rate, and specific growth rate of HCC2, while increasing serum lactate LDH, TG, and ALB and decreasing GLU, LDL-C, ALT, AST, and ALP levels. Dietary TPs supplementation enhanced antioxidant capacity (T-AOC, SOD, CAT, and GSH) and alleviated lipid metabolic disorders by activating the Nrf2/Keap1 and PPARα signaling pathways, thereby upregulating the expression of liver antioxidant genes (CAT and SOD) and fatty acid oxidation genes (CPT1 and acox1). Furthermore, intestinal microbiota analysis revealed that chronic crowding stress significantly increased the abundance of Proteobacteria and decreased the proportion of Firmicutes compared to the low-density control. Dietary TPs intervention, particularly at higher doses, partially restored the Firmicutes abundance and reduced the enrichment of potential pathogenic bacteria associated with stress. This study is the first to comprehensively elucidate the mechanism by which TPs alleviate crowding stress through enhanced antioxidant capacity, metabolic regulation, and microbiota remodeling, providing robust theoretical support for the application of plant-based additives in aquaculture.